Collisional relaxation kinetics for ortho and para NH2− under photodetachment in cold ion traps. (20th September 2018) - Gianturco, Francesco A.; Lakhmanskaya, Olga Y.; Vera, Mario Hernández; Yurtsever, Ersin; Wester, Roland
Abstract : Computational modeling and selective photodetachment experiments allow us to match the global temporal evolution of anions' losses in a trap with the selective losses estimated from theory. Abstract : The collisional cooling of the internal rotational states of the nonlinear anion NH2 − ( 1 A1 ), occurring at the low temperature of a cold ion trap under helium buffer gas cooling, is examined via quantum dynamics calculations and ion decay rate measurements. The calculations employ a novel ab initio potential energy surface that describes the interaction anisotropy and range of action between the molecular anions and the neutral He atoms. The state changing integral cross sections are employed to obtain the state-to-state rate coefficients, separately for the ortho - and the para -NH2 − ions. These rates are in turn used to compute the state population evolution in the trap for both species, once photodetachment by a laser is initiated in the trap. The present work shows results for the combined losses of both species after the photodetachment laser is switched on and analyzes the differences of loss kinetics between the two hyperfine isomers.